The Effectiveness of Zakat Distribution at the National Zakat Agency - Kamaludin Yusup, Deni; Sobana, Dadang Husen; Fachrurazy, Fachrurazy (Universitas Islam Negeri Raden Intan Lampung, 2021)
The effectiveness of zakat management in Indonesia can be seen from how far the zakat funds can be collected and properly distributed to the right people (mustahiq) by the zakat management agencies. This study aims to determine the extent of the collection, management, and distribution of zakat and its effect on the efficiency of zakat distribution by the National Zakat Agency in the 2008-2019 periods. This research uses the combination of qualitative and quantitative research, which the data source refers to the annual financial report of the National Zakat Management Agency in the 2008-2019 periods. Analysis of the Data uses the descriptive-qualitative and statistical-quantitative through correlation and linear regression tests. The results of this study show: first, the regulation of zakat has not been fully implemented in practice, so that the distribution of zakat has no positive and significant effect on the efficiency of zakat distribution; second, the role of zakat management institutions has no significant effect on the efficiency of zakat distribution in Indonesia; and third, the distribution of zakat and the role of zakat management institutions have no simultaneously positive and significant effect on the efficiency of zakat distribution in Indonesia, which is shown through the results of the significance test (F test) and the coefficient of determination test, as evidenced by the calculation results of the determination test only 19.1%, while the remaining 80.9% are other factors that are not studied. The implication of the results of this study is the management of zakat management must be improved so that its distribution becomes more effective and efficient.